Application of Virtual Sevima Edlink Class with Inductive Approach to Solving Math Problems Class X MA Mamba'ul Ma'arif - Khusnul Khotimah; Nur Faizah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This research is a quasi-experimental quantitative study that focuses on solving mathematical problems with inductive approaches to experimental classes that apply virtual classes to edlinks while control classes with conventional classes. The population in this study is class X-A and X-B MAS Mamba'ul Ma'arif School Year 2021-2022. The population will be sampled in the study. The purpose of this study is to find out if the application of sevima edlink virtual class is better than conventional class with inductive approach in solving math problems of class X MAS Mamba'ul Ma'arif. Based on the results of statistical calculations using SPSS 21 application, on the results of pretest data and posttest hypothesis test using Independent Sample t-test obtained value which means that solving math problems through experimental classes with the sevima edlink app is better than a control class with conventional learning. Advice for other researchers sevima edlink application is the right application used to build and improve the ability to solve math problems and can also be used for all subjects at the high school level (SMA) equivalent.